Recycling Waste of Rice Husk to Improve Entrepreneurship Motivation - Fatwa Tentama; Surahma Asti Mulasari; Muchsin Maulana; Rini Anggraeni (International Journal of Public Health Science (IJPHS), 2016)
The farmers in Indonesia have not maximally taken advantage of the existence of rice husk; therefore the huge number of the husk becomes disturbing waste, which spoils environment. The waste of rice husk is potentially capable of improving the farmers’ economy amidst the people’s lack of knowledge about its potential to commercially produce charcoal briquettes from it, make it a plant growing medium, and change it into manure. This research aims at knowing if the training of recycling waste of rice husk can improve the farmers’ entrepreneurship motivation. The subjects of the research were farmers in groups at Bimomartani village, Ngemplak district, Sleman regency. They were 60 participants divided into experintal and control groups. The planned experiment used untreated control group design with dependent pretest and posttest samples. The paired sample t-test and independent sample t-test were used as the techniques of analysis in this research. The result of t-test on paired sample t-test for the experimental group resulted in the value of t = -6.659 with p = 0.000 (p<0.01), which means there was a significant difference of entrepreneurship motivation before and after the training of recycling rice husk. The analysis for Independent sample t-test resulted in the value of t = 7.411 with p = 0.000 (p<0.01), which means there was a significant difference of entrepreneurship motivation between experimental and control groups. It can be concluded that the training of recycling waste of rice husk was effective in improving the farmers’ entrepreneurship motivation.